Post-edukacja i antyintelektualizm jako zjawiska kulturowe - Drozdowicz , Jarema (Studia Edukacyjne, 2019)
This paper makes the attempt to highlight the role played in contemporary education by the notion of post-truth and the influence played in that matter by anti-intellectual tendencies. This issue seems to be imperious in the face of transformation tendencies of the schooling systems and the influence exerted by the world of politics in that context. This text reconstructs the most important aspects of the anti-intellectual stance, treating it as a specific phenomenon of a cultural nature. Furthermore, the emerging issue of post-education is addressed as it accompanies the anti-intellectual tendencies and strengthens their impact on the schooling level. Both issues are in a clear cause-and-effect relation to the phenomenon of post-truth.